New Insights into the Neurobiology of Restless Legs Syndrome. (April 2019) - Ferré, Sergi; García-Borreguero, Diego; Allen, Richard P.; Earley, Christopher J.
Restless legs syndrome (RLS) is a common sensorimotor disorder, whose basic components include a sensory experience, akathisia, and a sleep-related motor sign, periodic leg movements during sleep (PLMS), both associated with an enhancement of the individual's arousal state. The present review attempts to integrate the major clinical and experimental neurobiological findings into a heuristic pathogenetic model. The model also integrates the recent findings on RLS genetics indicating that RLS has aspects of a genetically moderated neurodevelopmental disorder involving mainly the cortico-striatal-thalamic-cortical circuits. Brain iron deficiency (BID) remains the key initial pathobiological factor and relates to alterations of iron acquisition by the brain, also moderated by genetic factors. Experimental evidence indicates that BID leads to a hyperdopaminergic and hyperglutamatergic states that determine the dysfunction of cortico-striatal-thalamic-cortical circuits in genetically vulnerable individuals. However, the enhanced arousal mechanisms critical to RLS are better explained by functional changes of the ascending arousal systems. Recent experimental and clinical studies suggest that a BID-induced hypoadenosinergic state provides the link for a putative unified pathophysiological mechanism for sensorimotor signs of RLS and the enhanced arousal state.